Asphalt Modification Using Low Liniear Density Polyethylene (LLDPE) Plastic And Cigarette Butt Filter Waste - Joshua Edward Rolando Sutantio; Yosef Cahyo Setianto Poernomo; Ahmad Ridwan; Rendy Kurnia Dewanta; Haris Wicaksono (Litbang Pemas - Universitas Islam Lamongan, 2021)
The development of technology in the transportation sector is increasingly advanced, many renewable innovations are continuously being developed. Various studies have been carried out to find the best solution for finding new innovations. The management of LLDPE plastic waste and cigarette filters into a modified asphalt mixture is an example of a renewable technology. The purpose of this study was to determine the impact of adding LLDPE plastic waste and cigarette filters into the modified asphalt mixture, with a variation of 20% LLDPE and cigarette filters 5%, 10%, 15%. The results showed that the addition of the mixture to the modified asphalt, there was a decrease in the value of Stability, MQ, VIM, VMA, VFB, and Flow.